THE DESCRIPTION OF THE QUALITY OF HEALTH SERVICES TO PATIENT SATISFACTION - M. Fais Satrianegara; Azriful Azriful; Zilfadhilah Arranury; Nur Azisah Anwar (Universitas Islam Negeri Alauddin Makassar, 2020)
Background: Quality health services are health services that can satisfy every service user by the average satisfaction level of the population and its implementation by the established code of ethics and service standards. Objective: To determine the description of the quality of health services on patient satisfaction in the inpatient installation of the Makassar General Hospital of the Hajj Region in 2019.Method: The method used is descriptive. The population in this study were patients using inpatient class III RSUD Haji Makassar in 2019 and based on data obtained in May 2019 as many as 848 patients.Result:The satisfaction service variable shows that of the 89 samples studied, 80 respondents were satisfied (89.9%) and 9 respondents (10.1%) were dissatisfied. The reliability variable (57.3%) is categorized as good and (42.7%) is not good. The responsiveness variable (66.3%) is categorized as good and (33.7%) is not good. The guarantee variable (75.3%) is categorized as good and (24.7%) is not good. The direct evidence variable (53.9%) is categorized as good and (46.1%) is not good. The empathy variable (82.0%) is categorized as good and (18.0%) is not good.Conclusion: It is hoped that the health workers at the General Hospital of the Haji Makassar Region will improve performance in prime health service activities to the community, and always prioritize the interests of patients in installations, especially patients in inpatient installations.